EFFECT OF THE HEAT TREATMENT OF Hovenia dulcis Thunb. WOOD ON THE PRODUCTION OF EGP PANELS WITH DIFFERENT ADHESIVES - Marchesan, Raquel; Toledo Corrêa dos Santos, Edison; Trianoski, Rosilani; França, Morgana Cristina; Loiola, Pedro Licio; Vinha Zanuncio, Antônio José (Floresta, 2020)
The objective of this work was to analyze the shear strength of edge-glued panels (EGP) made from the H. dulcis Thunb. wood thermally modified by the VAP HolzSysteme® process. Initially, the Hovenia dulcis samples were heat-annealed by the VAP HolzSysteme® process, and then bonded with Resorcinol-formaldehyde (RF), Melamine-urea-formaldehyde (MUF), Isocyanate Polymer Emulsion (EPI) and Polyvinylacetate (PVAc) and submited to pre-treatments for dry, humid and external environment and without pre-treatment to evaluate the shear strength, 5th percentile and failure in the wood. It was observed a decrease in the shear strength of the thermorrectified H. dulcis wood for all adhesives. All adhesives obtained results superior to the minimum required by the standard EN13354 (2009) for the wood without pre-treatment as for the wood without thermoregulation as well as for the heat treated wood, and may be used for non-structural purposes. However, for the external environment (three cycles) only the MUF adhesive obtained value that meets the minimum standards of the standard, in this way, it is suggested to glue the EGP of H. dulcis without thermortification and with thermorrectification using the MUF adhesive, which has achieved better performance offering greater resistance in dry, wet and external environments.